Negrifeminicídio: O feminicídio de mulheres negras no estado de São Paulo - Carvalho, Alicia Scordamaia de (Universidade Federal de São Carlos, 2024)
Violence against women and racism are extremely important issues that must be addressed with great care and seriousness. In this work, they will be presented together: the violent deaths of white and black women and their differences in the state of São Paulo, where the Federal University of São Carlos is located. Through Generalized Linear Models of Poisson distribution, the evolution of the number of violent deaths of women in four different periods will be studied: before the enactment of the Maria da Penha Law; from the enactment of the Maria da Penha Law to the enactment of the Femicide Law; from the enactment of the Femicide Law to the decree of the Covid-19 pandemic; and the Covid-19 pandemic decree until the end of 2021. In addition to the influence of the enactment of laws and the Covid-19 Pandemic, other factors such as Schooling, Marital Status, Age and Place of Occurrence of death will also be studied, and how these factors separately influence, and in each period, the violent death of Black and White women in the state of São Paulo from 1999 to 2021.
Negrifeminicide: The feminicide of black women in the state of São Paulo
Keywords: Feminicídio; Poisson; Pandemia; Feminicide; Pandemic; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA::ANALISE DE DADOS